Atomization and evaporation process of liquid fuel jets in crossflows: A numerical study using Eulerian/Lagrangian method. (August 2020) - Wen, Jian; Hu, Yong; Nakanishi, Akihiro; Kurose, Ryoichi
Highlights: Lagrangian tagging methodis concerned for reducing the computational cost. Three different breakup modes in different aerodynamic Weber are reproduced by the CLSVOF method. The vortex analysis behind the liquid column indicates the distinct bifurcating jets result from the existence of SBV. The evaporation effects are found dominated by the SBV morphology in different aerodynamic Weber number. Abstract: Liquid fuel atomization in transverse uniform gaseous flow, i.e., crossflow, is widely utilized in aircraft engines and is considered an important aspect for engine development. The atomization-evaporation process of liquid fuel jet spray in the vicinity of a nozzle in crossflows is investigated by a detailed numerical simulation using an Eulerian/Lagrangian framework. The Eulerian framework is applied for each gas and liquid continuum fluid phase, whereas the Lagrangian framework is applied for the dispersed droplets generated by the atomization process. To capture the gas-liquid interface with an accurate surface tension in the Eulerian framework, a coupled Levelset and volume-of-fluid (CLSVOF) method is used. The evaporation of Lagrangian droplets is considered by a non-equilibrium Langmuir-Knudsen evaporation model. The results show that the trends of the jet trajectory and primary breakup behavior of liquid column are well captured and in good agreements with the previous experimental and analytical studies. The aerodynamic Weber number significantly influences the primary breakup behavior and the vortex development and morphology behind the liquid column, which tends to drastically change the evaporation process as well.